Pembelajaran Berbasis Proyek “Mas Bei” untuk Meningkatkan Aktivitas Belajar IPS - Sumarjo Sumarjo (Balai Teknologi dan Komunikasi Pendidikan DIY, 2025)
A professional teachers are required to have pedagogical competence, personal competence, social competence, and professional competence. Evidence of this competence, among others, is shown by the teacher describing his teaching experience in a classroom action research report (CAR). One of the learning problems is that students are passive during learning. This research is an effort to prove that project-based learning treatment can increase student learning activities. This is proven by assignments and presentations with kinemasters and assignments to find scholarship information, which are able to increase student learning activities. The application of the project-based learning model